Comparative study of inhibition mechanisms of structurally different flavonoid compounds on α-glucosidase and synergistic effect with acarbose. (15th June 2021) - Yang, Jichen; Wang, Xiaoli; Zhang, Chuanying; Ma, Lun; Wei, Tao; Zhao, Yajing; Peng, Xin
Abstract: Flavonoid compounds have anti-diabetic activity, which can control blood glucose levels by inhibiting α-glucosidase activity. In this paper, the inhibition mechanisms between four flavonoid compounds and α-glucosidase were studied by multispectroscopic methods and molecular docking. The results showed that the inhibitory activities of flavonoid compounds were higher than that of acarbose, and the sequence of inhibition effect was scutellarein > nepetin > apigenin > hispidulin > acarbose. Also, the synergistic effects of flavonoid compounds combined with acarbose on inhibiting α-glucosidase activity were observed. The fluorescence results showed that flavonoid compounds combined with α-glucosidase to form a stable complex. And the spectral analysis indicated that the microenvironmental and secondary structure of α-glucosidase were changed. The present study demonstrated that the molecular structure of flavonoid compounds played an important role in the inhibition process, namely, scutellarein with more hydroxyl groups on the A-ring might serve as the most effective α-glucosidase inhibitor.